Going Places : facilitating good practice in international social work student exchange in Australia and the Indo-Pacific. Final report 2018. - Miles, Debra; Howard, Elise; Puthantharayil, George; Dhephasadin Na Ayudhaya, Piyachat; Harris, Nonie; Jones, Peter; Zuchowski, Ines; Macknight-King, Julie; Francis, Abraham; Gopalkrishnan, Narayan (Australia. Dept of Education and Training (DET), 2018)
Focusing on enhancing relationships with the Indo-Pacific, this project aimed to: identify, describe and disseminate current practice in international student exchange in Australian schools of social work; develop a framework for embedded and respectful approaches to international student exchange that facilitate values of reciprocity and mutuality between Australian social work programs and hosting partners in the Asia Pacific; and disseminate illustrative resources and guidelines, including an ethical practice guide to support and facilitate the integration of international student exchange programs into social work curricula. The methodology involved multiple data sources including a literature review, a survey, interviews and workshops. Findings were that social work staff were more likely to be responsible for organising exchange activities than mobility officers. Partnerships with international universities or organisations were most frequently initiated through personal relationships, or relationships between schools of social work. Overall, hosts reported exchange activity in a positive light; however, evidence of inequitable partnerships exists. Australian organisations often regarded hosts as useful for cultural knowledge or local connection to facilitate student research, yet not as equals in knowledge exchange on discipline specific areas. Hosts reported that the continual workload of exchange and the cumulative effect of hosting students, including the continuous commitment required to manage student safety, often lacked acknowledgement in the resourcing of exchange programs. Exchange partners must acknowledge and understand values, social structures and political conditions as well as the historical relationship between sending and hosting countries. Sustainable approaches to internationalisation and authentic relationships are vital elements of ethical international student exchange; despite rhetorical commitment to internationalisation within universities, many staff reported a lack of support from structures within universities, no workload allocation and little financial support. Little support was offered after the exchange to maintain relationships that contributed to the exchange experience. Exchange experiences are regarded as more sustainable when degrees or subjects are collaboratively designed, including opportunities for placement or work-integrated learning. Thorough and ongoing evaluation of the supports and structures surrounding exchange programs is required. Regarded as important opportunity by both hosting and sending organisations to promote sustainability is formalising partner arrangements with agreed forums such as a memorandum of understanding. The survey and research findings of this project informed the development of principles detailed within the practice guide and additional resources including: engage with historical, structural, sociopolitical, cultural, ecological and professional contexts; embed exchange within sustainable internationalisation; foster authentic relationships; commit to reciprocal partnerships; apply a critical lens to intercultural learning and global perspectives; and facilitate and guide transformative learning.